Correlation Between Patients With Methicillin-Resistant Staphylococcus aureus (MRSA) Nares Colonization and MRSA Diabetic Foot Infections. (December 2022) - Brondo, Jacquelyn; Morneau, Kathleen; Hopkins, Teri; Yang, Linda; Cadena-Zuluaga, Jose; Walter, Elizabeth
Infectious Diseases Society of America diabetic foot infection (DFI) guidelines indicate empiric methicillin-resistant Staphylococcus aureus ( MRSA) coverage for patients with a history of MRSA infection, when local prevalence of MRSA is high, or infection is clinically severe. These recommendations may lead to overutilization of empiric MRSA coverage, which can result in serious consequences. A strong negative predictive value (NPV) has been reported in literature for pneumonia, and recently, for all anatomical sites of infection. While these findings are promising, further validation is needed before clinicians may confidently use MRSA nares to guide empiric therapy for DFIs. A retrospective electronic medical record review was completed between October 1, 2013 and October 1, 2019. Patients met inclusion criteria if they were at least 18, admitted with a DFI, had MRSA nares test results, and DFI cultures. Patients were excluded if pregnant or MRSA infection within 1 year prior to index admission for DFI. A total of 200 patients met inclusion criteria. The majority of study participants were male with a mean age of 63. NPV of MRSA nares for MRSA DFIs was determined to be 94% and positive predictive value 58%. Sensitivity and specificity were 56% and 94%, respectively. Results of this study are consistent with prior literature supporting strong correlation of NPV for MRSA nares. The DFIs evaluated suggest a strong NPV of MRSA nares for MRSA DFIs, which may allow for faster de-escalation of empiric anti-MRSA antibiotic therapy and lower risk of adverse events associated with anti-MRSA therapy.